Mathematical modelling of pipeline composite repair design using finite element analysis incorporating putty's contribution - Sim, Yu Ling (2019)
A composite repair system which consists of Fibre Reinforced Polymer (FRP) and putty as infill material has been proven effective in repairing pipeline system. However, previous studies including the design codes and standards are neglecting the contribution of putty as they assume putty is only functioned to fill the corroded section and to transfer loads from damaged pipeline to composite wrap. This has restricted the efforts to explore the contribution of putty that performance of wrapper became the main focus in the past research works. A recent study has pointed out that putty is not only limited to transfer the load, but it has the potential to serve as a load bearing component. Therefore, this research is aimed to model the contribution of putty in terms of load bearing capacity through finite element analysis (FEA) and mathematical modelling. Two finite elements models were utilized to study the performance of two different material properties of putties used to repair externally corroded pipeline followed by regression analysis. The relationship between burst pressure and stress distribution of steel, composite wrap and putty are investigated. Results revealed that different properties of putty have great influence upon the behaviour and subsequently the overall performance of a composite repaired pipe. A high tensile strength putty can increase the burst capacity that a repaired pipe can withstand by providing additional reinforcement while high tensile modulus of putty can help to reduce the deformation. In addition, it was found that by incorporating the strength contribution of putty, there are potential to increase the burst pressure by about 5%. The finding of this research is significant as it provides comprehensive understanding on the contribution of putty in terms of load bearing capacity in composite repaired pipeline where its contribution has been quantified with two different properties of putties. Hence, the inclusion of strength contribution of putty should be taken into account in the closed-form solution of composite repair design. This can serve as a stepping stone towards design optimization of pipeline rehabilitation, such as minimizing the usage of composite wrap and subsequently repair without composite wrap.